Neurocognitive dysfunction among HIV positive patients using International HIV dementia scale - Achappa, Basavaprabhu; Priyadarshni, Shivani; Madi, Deepak; Bhaskaran, Unnikrishnan; Ramapuram, John T; Rao, Satish; Chowta, Mukta N; Mahalingam, Soundarya (Asian Journal of Medical Sciences, 2014)
Background: HIV associated neurocognitive dysfunction (HAND) ranges from asymptomatic neurocognitive impairment (ANI) to mild neurocognitive disorders (MND) to HIV associated dementia (HAD). Cognitive impairment may impact medication adherence which will ultimately affect morbidity and mortality. Aim: This study was undertaken to evaluate neurocognitive dysfunction among HIV positive patients using the International HIV Dementia scale(IHDS). Materials and Methods: This cross sectional study was conducted in a tertiary care hospital attached to a medical college that caters to a large number of HIV positive patients. The subjects for this study included HIV positive patients belonging to WHO stage 1 or 2. Data collection was done using a pre tested questionnaire. The International HIV Dementia scale(IHDS) was used to assess HAND. Results: Out of the 101 patients studied, 69(68.3%) were males and 32(31.7%) were females. Among these patients, 88 (87.1%) were receiving antiretroviral therapy (ART), 84 (83.2%) were in WHO stage 1. 91 (90.1%) patients had HAND. There were statistically significant differences in the gender and educational level between patients with or without HAND. As age advanced the percentage of patients having HAND also increased. Conclusion: There was high prevalence of HIV associated neurocognitive dysfunction among HIV positive individuals in our study. Also there was an increase in HIV associated neurocognitive dysfunction with increase in age. DOI: http://dx.doi.org/10.3126/ajms.v5i4.8724 Asian Journal of Medical Sciences 2014 Vol.5(4); 61-64